A Novel ALAS2 Missense Mutation in Two Brothers With Iron Overload and Associated Alterations in Serum Hepcidin/Erythroferrone Levels - Lira Zidanes, Acaynne; Marchi, Giacomo; Busti, Fabiana; Marchetto, Alessandro; Fermo, Elisa; Giorgetti, Alejandro; Vianello, Alice; Castagna, Annalisa; Olivieri, Oliviero; Bianchi, Paola; Girelli, Domenico (Frontiers in Physiology, 2020)
Iron loading anemias are characterized by ineffective erythropoiesis and iron overload. The prototype is non-transfusion dependent ß-thalassemia (NTDT), with other entities including congenital sideroblastic anemias, congenital dyserythropoietic anemias, some hemolytic anemias and myelodysplastic syndromes. Differential diagnosis of iron loading anemias may be challenging due to heterogeneous genotype and phenotype. Notwithstanding the recent advances in linking ineffective erythropoiesis to iron overload, many pathophysiologic aspects are still unclear. Moreover, measurement of hepcidin and erythroferrone (ERFE), two key molecules in iron homeostasis and erythropoiesis, is scarcely used in clinical practice and of uncertain utility. Here, we describe a comprehensive diagnostic approach, including next-generation sequencing (NGS), in silico modelling, and measurement of hepcidin and erythroferrone (ERFE), in two brothers eventually diagnosed as X-linked sideroblastic anemia (XLSA). A novel pathogenic ALAS2 missense mutation (c.1382T>A p.Leu461His) is described. Hyperferritinemia with high hepcidin-25 levels (but decreased hepcidin:ferritin ratio) and mild-to-moderate iron overload were detected in both patients. ERFE levels were markedly elevated in both patients, especially in the proband, who had a more expressed phenotype. Our study illustrates how new technologies, such as NGS, in silico modelling, and measurement of serum hepcidin-25 and ERFE may help in diagnosing and studying iron loading anemias. Further studies on the hepcidin-25/ERFE axis in additional patients with XLSA and other iron loading anemias may help in establishing its usefulness in the differential diagnosis, as well as to better understand pathophysiology of these genetically and phenotypically heterogeneous entities.